2018
DOI: 10.1038/s41598-018-31304-w
|View full text |Cite
|
Sign up to set email alerts
|

Scans for signatures of selection in Russian cattle breed genomes reveal new candidate genes for environmental adaptation and acclimation

Abstract: Domestication and selective breeding has resulted in over 1000 extant cattle breeds. Many of these breeds do not excel in important traits but are adapted to local environments. These adaptations are a valuable source of genetic material for efforts to improve commercial breeds. As a step toward this goal we identified candidate regions to be under selection in genomes of nine Russian native cattle breeds adapted to survive in harsh climates. After comparing our data to other breeds of European and Asian origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 122 publications
7
89
1
2
Order By: Relevance
“…A number of reports have suggested that ribosomal proteins are essential for survival and adaptation to environmental stress [75][76][77] . For example, one of the ribosomal proteins we found was the ribosomal large subunit protein 7 (RPL7), which has been previously reported in Russian cattle breeds 78 to be related to adaptation to harsh (cold) environments. The ribosomal large subunit protein 7 (RPL7) gene was found to be upregulated in the skin of freeze-tolerant wood frogs compared to non-tolerant species, showing that this gene is cold-responsive and that the gene was upregulated in skeletal muscle and the brain under freezing stress 77 .…”
Section: Discussionsupporting
confidence: 54%
“…A number of reports have suggested that ribosomal proteins are essential for survival and adaptation to environmental stress [75][76][77] . For example, one of the ribosomal proteins we found was the ribosomal large subunit protein 7 (RPL7), which has been previously reported in Russian cattle breeds 78 to be related to adaptation to harsh (cold) environments. The ribosomal large subunit protein 7 (RPL7) gene was found to be upregulated in the skin of freeze-tolerant wood frogs compared to non-tolerant species, showing that this gene is cold-responsive and that the gene was upregulated in skeletal muscle and the brain under freezing stress 77 .…”
Section: Discussionsupporting
confidence: 54%
“…2018; Yurchenko et al . 2018). For the POLLED (hornless) trait, four genetic variants have been identified in an intergenic region of BTA1 (Aldersey et al .…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%
“…É ‡flÎ˚ fl‚-Îfl˛ÚÒfl ˆÂÌÌ˚ÏË ÊË‚ÓÚÌ˚ÏË ‰Îfl ÒÍ¢˂ ‡ÌËfl Ò ÏÂÒÚÌ˚Ï ÒÍÓÚÓÏ, Ì ‡ÔËÏÂ, Ò B. indicus ‚ ‚ÓÒ-ÚÓ˜ÌÓÈ ˜ ‡ÒÚË ÅÛÚ ‡Ì ‡ Ë ÄÛÌ ‡˜ ‡Î è ‡‰Â¯ ‡. ÉË•-ˉ˚ ÔÂ‚Ó"Ó ÔÓÍÓÎÂÌËfl, ÔÓÎÛ˜ÂÌÌ˚Â Ò Û˜ ‡ÒÚËÂÏ ÏÂÒÚÌ˚ı ÔÓÓ‰, ËÁ‚ÂÒÚÌ˚ Í ‡Í flÚ¯ ‡ (Jatsha -ÏÛÊ-ÒÍÓÈ) Ë flÚ¯ ‡Ï (Jatsham -ÊÂÌÒÍËÈ ÔÓÎ èÓÒΉÌË ‰ ‡ÌÌ˚ ÔÓÎÌÓ"ÂÌÓÏÌÓ"Ó ÒÂÍ‚ÂÌË-Ó‚ ‡ÌËfl ÁÌ ‡˜ËÚÂθÌÓ ÛÎÛ˜¯ËÎË Ô‰ÒÚ ‡‚ÎÂÌËfl ˝‚Ó-βˆËË ˝ÚËı ÍÛÔÌ˚ı ÍÓÔ˚ÚÌ˚ı Ë ÔÓÏÓ"ÎË ÔÓ-ÎËÚ¸ Ò‚ÂÚ Ì ‡ ÒÎÓÊÌ˚È ÔÓˆÂÒÒ Ó‰ÓÏ ‡¯ÌË‚ ‡ÌËfl Ë ‡‰ ‡ÔÚ ‡ˆËË ˝ÚËı ‚ˉӂ, "ÂÌÂÚ˘ÂÒÍËı ÔÓÚÓÍÓ‚ ÔË ÙÓÏËÓ‚ ‡ÌËË  ‡ÁÌ˚ı ÔÓÓ‰ ÍÛÔÌÓ"Ó Ó" ‡ÚÓ"Ó ÒÍÓÚ ‡, ÚÂÒÌÓ"Ó Û˜ ‡ÒÚËfl, ‚ ˜ ‡ÒÚÌÓÒÚË, Á•ۂˉÌÓ"Ó ÒÍÓÚ ‡ ‚ ÙÓÏËÓ‚ ‡ÌËË fl‰ ‡ ‚ÓÔÂÈÒÍËı ÔÓÓ‰ [11,16,25,26,27]. Ç ÚÓ Ê ‚ÂÏfl, ÏÌÓ"Ë ‡ÒÔÂÍÚ˚ "ÂÌÂÚ˘ÂÒÍËı ‚Á ‡ËÏÓÓÚÌÓ¯ÂÌËÈ ÏÂÊ‰Û Ô‰ÒÚ ‡‚ËÚÂÎflÏË Ó‰ ‡ «Ì ‡ÒÚÓfl˘Ëı» •˚ÍÓ‚ ‰Ó ÒËı ÔÓ ÓÒÚ ‡˛ÚÒfl ‰ÓÒÚ ‡ÚÓ˜-ÌÓ ÔÓÚË‚Ó˜˂˚ÏË.…”
Section: é ‡Flî ë áâ•ûunclassified